The relationship between the reader’s interest and comprehension - Busakwe, Gontse (My University, 2022)
In South Africa, 78% of Grade Four learners cannot read for meaning (PIRLS, 2017). The purpose of this study was to understand this reading comprehension crisis through a different lens. This study aims to investigate whether interest in the text affects the learners’ ability to understand what they are reading in a Grade 3 South African classroom. I will begin by analysing the most common graded readers learners in grade 3 public schools engage with, in order to establish their relevance to the learners. This analysis will be followed by a case study of Grade 3 learners’ reading comprehension on two sets of readers of the same level. One set of readers will be selected from the Biff, Chip and Kipper (1986, Oxford Reading Tree) series which form part of their classroom guided readers library read at their school and the second set of readers will include books written by South African author, Niki Daly. I have chosen Niki Daly’s books because he is well known for writing children’s books which are contextually relevant to the South African child whereas the former are arguably not contextually relevant. This information will assist in understanding the relationship between the readers’ interest and comprehension which I will gather through the comprehension tasks and interviews with the learners after they have read the books. Based on the results from the case study it was clear that interest does affect reading achievement. Learners who had an interest in the books they read received higher reading comprehension scores, showing higher reading competencies.
A research report presented in partial fulfilment of the requirement for the degree of Masters in Education by Coursework and Research Report to the Faculty of Humanities, School of Education, University of the Witwatersrand, 2022